Impulsive Control of the Rotor-Stator Rub Based on Phase Characteristic - Jieqiong Xu; Qunhong Li; Shimin Wang (Abstract and Applied Analysis)
An impulsive control method is proposed to eliminate the rotor-stator rubbing based on the phase characteristic. The relation between the vibration energy and the phase difference suggests the starting point for controlling the rotor-stator rubbing by implementing impulse. When the contact between the rotor and the stator occurs, the impulse is implemented in x-direction and y-direction several times to avoid the rotor-stator rubbing. The practical feasibility of this approach is investigated by numerical simulations.